Energy and the Quality of Life Understanding Energy Policy - Hooker, Clifford; Macdonald, Robert; van Hulst, Robert (Heritage, 1981)
As the supply/cost crunch tightens, issues related to energy become increasingly compelling. This is a guide for the general public to the fossil fuel crisis facing Canada, and Ontario in particular. It is also about other long-term matters of greater importance: the economic, socio-political, and cultural consequences of the choices which now have to be made, primarily by governments. The authors argue that energy policy is social policy. Therefore our ideas about the kind of society we want must be a governing consideration in working out a policy to take Canada through the energy crisis. The four writers bring to bear on the problem the perspectives of engineering, philosophy, environmental studies, and economics. The result is a balanced guide for the continuing debate on the adaptation of society to the imperatives of energy